The brink of peace : the Israeli-Syrian negotiations - Rabinovich, Itamar, 1942- (Princeton University Press, 1998)
A major casualty of the assassin's bullet that struck down Israeli Prime Minister Yitzhak Rabin was a prospective peace accord between Syria and Israel. For the first time, a negotiator who had unique access to Rabin, as well as detailed knowledge of Syrian history and politics, tells the inside story of the failed negotiations. His account provides a key to understanding not only U.S. diplomacy in the Middle East but also the larger Arab-Israeli peace process. During the period from 1992 to 1996, Itamar Rabinovich was Israel's ambassador to Washington, and the chief negotiator with Syria. In t.